Giving of Media Modules Reviewed from Personal Hygiene Against Capitis Pediculose Incidence in Islamic Boarding School of Al-Fattahiyyah Tulungagung - Prima Dewi; Ikko Ambar Noviana (International Conferences SDGs 2030 Challenges and Solutions, 2030)
Capitis Pediculose is one of the health problems that cause interference in the child's hair resulting in decreased learning achievement. Students who have Capitis Pediculose one cause is lack of personal hygiene. The purpose of this study was to determine the effect of media module on the occurrence of Capitis Pediculose. Pre-experimental research design is with posttest only. Sampling technique with Total Sampling got sample of 53 respondents. Independent variable of module media, dependent variable of Capitis Pediculose incidence, data collected by observation, analysis with Binomial Test with α = 0,05. The results showed most respondents who experience Capitis Pediculose after given media module in the category did not happen that is 40 respondents (75.47%). The result of data analysis with Binomial Test shows that the significance level = 0,000 α = 0.05 H0 is rejected which means there is influence of module media to the occurrence of Capitis Pediculose in the Islamic Boarding School of Al-Fattahiyyah Tulungagung. Suggestion for cottage girls is to make efforts to eradicate or prevent Capitis Pediculose.